The Effect of Processing Parameters on Physical Properties and Mechanical Properties in the Mixture of Pristine HighDensity Polyethylene (HDPE) with Regrind Material Using Simple Injection Molding Machines - Fiardhi, Wahyu
High-density polyethylene (HDPE) is a material that is often used to make plastic products. In the production of HDPE in the large-scale plastic products industry, reject and residual production scraps are produced which are then chopped to be reprocessed with pure material (pristine HDPE) with a certain ratio. The chopped material is regrind material. The method of processing plastic products that is often used in industry is injection molding This processing method can produce various kinds of products because it can produce products with complex shapes, production can be done in bulk, and high production capacity. A simple injection molding machine is a machine that can be used for processing injection molding but is not complicated with a small production capacity. In this study, it was studied the reuse of regrind HDPE obtained from the plastic industry in Indonesia to make products using a simple injection molding machine. The initial stage of the research is the determine of Window Temperature Processing. then followed by determining the mixture fraction and tensile testing and also determining the mixture density of pristine HDPE and regrind HDPE. The Window Temperature Processing was made to map the processing temperature of pristine HDPE (130-190oC) with an average tensile strength of 21.74 MPa and processing temperature of regrind HDPE (170-280oC) with an average tensile strength of 22.07 MPa. Then, from the processing temperature window of each material, the optimum processing temperature is determined, which is at 150oC, 170oC, 180oC, 190oC, and 210oC, then processing pristine HDPE and regrind HDPE mixture at various composition fractions at each temperature. The optimum regrind fraction is obtained by looking at its tensile strength, which is at 60% regrind HDPE fraction. In addition, by reviewing the fractions of 0%, 60%, 90%, and 100% a density test is carried out. From the results of the density test analysis it can be concluded that the mixture density follows the rule of mixture with pristine HDPE density at 0.9304 g/cm3 and regrind HDPE at 0.9443 g/cm3. In this study it was concluded that regrind HDPE is very potential to be reused to make good quality products using a simple injection molding machine.